Conservation strategy for Taxus sumatrana, a species with limited geographical distribution yet limitless benefit and economic value. Issue 1 (August 2020) - Novriyanti, E; Susilo, A
Abstract: Taxus sumatrana is a pharmacologically essential tree species that have not yet adequately studied and commercially utilized in Indonesia yet recently was added in the List of Protected Plants and Animals by the government of Indonesia. This paper discussed the conservation strategy of the paradox situation. Protected species yet has not been utilized. T. sumatrana in Indonesia is distributed in a confined range of geographical areas and with particular environmental requirements. T. sumatrana allegedly occurs along unexplored Bukit Barisan Mountains. Biologically, the species is a slow-growing dioecious tree with prolonging seed dormancy period, lack of suitable regeneration site, leading to low generation capacity creating population dominated by tree stage with barely pole sapling and seedling. Genetically, the species own insignificant differences among the population. Strategy to conserve T. sumatrana should include an in-depth exploration of T. sumatrana in the natural habitat, improvement of regeneration capacity, revitalization and development of reserves based on genetic information, cultivation and development of plantation for sustainable utilization, campaign and promotion on sustainable utilization, stakeholder networking, and capacity building.